Tinjauan Pola Penggunaan Antibiotik Pada Pasien Anak Demam Tifoid di Instalasi Rawat Inap RSUP dr. Kariadi Semarang Tahun 2009 - Dian Anggraini, Truly (Jurnal Farmasi (Journal of Pharmacy), 2013)
Typhoid fever including one of disease the infection found many in developing countries with high density and also health of low environment. Pursuant to report WHO mentioned that Indonesia is one of the State with number occurence of high typhoid fever, that is > 100 per 100.000 resident per year. Epidemiology study is recently show to start the existence of risk multi drug resisten (MDR) at usage of antibiotic for the medication of typhoid fever. So that this research is done to know the pattern usage of antibiotic at typhoid fever child patient in Installation of Hospitalization RSUP Dr. Kariadi Semarang in the year 2009. This research is non-experimental. The data was collected retrospectively from patient medical records. Counted 100 sampel obtained, and the results were analyzed using descriptive non-analytic method. Patterns of use of antibiotics for typhoid fever seen through a class of antibiotics used, the presence or absence of antibiotics during replacement therapy, a combination of antibiotics given, route of administration, duration of antibiotics, antibiotic side effects, and drug interactions that occur due to the use of antibiotics. Research result indicate that at period of year of 2009 in Installation of Hospitalization RSUP Dr. Kariadi typhoid fever predominated by men patient at spanning the age of 6-10 year. The Antibiotic faction at most used is from faction sefalosporin equal to 55,22%, from 100 case of 35 between natural it’s of replacement antibiotic, usage of antibiotic combination equal to 50%, supply of antibiotic more given in the form of hypodermic and for the giving of antibiotic there are to don’t according giving of antibiotic at patient with written Standard Procedure Operational that is much more brief.